Multiple solutions for super-linear symmetric operator equations. (3rd June 2021) - Chen, Yingying
ABSTRACT: This paper investigates multiple solutions for super-linear symmetric operator equations by optimization methods like index theory, Mountain pass theorem and mini-max methods. Applying the results to second order Hamiltonian systems with symmetry yields finite or infinitely many solutions.